(untitled) (Journal of Partial Differential Equations, 2014)
" In this work, we study the following nonlinear homogeneous Neumann boundary value problem 03b2(u)2212diva(x,2207u) 220b f in 03a9, a(x,2207u)22c503b7 =0 on 220203a9, where 03a9 is a smooth bounded open domain in 211c^N, N 2265 3 with smooth boundary 220203a9 and 03b7 the outer unit normal vector on 220203a9. We prove the existence and uniqueness of an entropy solution for L00b9-data f. The functional setting involves Lebesgue and Sobolev spaces with variable exponent."